Additive Manufacturing of 3D Circuit Carriers with Improved Thermal Conductivity - Utsch, Daniel; Piechulek, Niklas; Franke, Jörg (45th International Spring Seminar on Electronics Technology (ISSE), 2022)
The ongoing demand for more powerful electronic assemblies requires the development of more flexible systems with substrates showing improved thermal and electrical properties. In this regard, fiber-filled polymers processed by Additive Manufacturing technologies are promising. While previous work rather focuses on the material and mechanical aspects of filled polymers and 3D printing, this work proposes an innovative approach to manufacture electronic assemblies additively using Fused Filament Fabrication with glass fiber-filled polymers to create 3D substrates and using digital printing technologies to create electrically conductive structures on the manufactured specimens. For this reason, a reduction of substrate surface roughness through systematic optimization of parameter configuration is necessary to print constant conductive lines subsequently. By this means, 3D circuit carriers for electronic assemblies with improved thermal conductivity can be produced completely additively. Surface roughness of Ra=2.6μm and Rz=42.0μm was achieved in this work, and the printed lines were qualified in optical, electrical, and mechanical regard.<br

Innovative robot tool for full-automatic handling and wiring of deformable linear cables - Fröhlig, Simon; Nguyen, Huong Giang; Piechulek, Niklas; Franke, Jörg (Procedia CIRP, 2023)
The manufacturing of complex cable systems e.g. for vehicle integration or the direct wiring inside control cabinets is a laborious, manual, and error-prone process. For cost optimization reasons, cable pre-assembly is carried out in the best-cost countries. Long supply chains and a lack of resilience in the cable industry have recently caused the re-location of the final assembly of mechatronic products to high-automation countries. This paper presents a robot-guided tool that enables automated feeding, insertion, and routing of confectioned cables. We developed a gripping device to handle cables as damage-sensitive handling objects. The cable is pneumatically gripped by a flexible surface and clamped to absorb the forces during the insertion process. In contrast to state-of-the-art grippers which are based on rigid gripping jaws, we show that a force-locked gripping mechanism can be realized without damaging and imprinting the cable insulation. In this paper, both the design of the gripping tool and the insertion process flow are presented. We tested the tool with a Fanuc CR15-iA robot in the laboratory environment. Our experimental results proved the technical feasibility and led to the deduction of potential improvements for further research.
CRIS-Team Scopus Importer:2024-12-16
Keywords: automatic wiring; deformable linear object; DLO-in-hole; flexible gripper; wire assembly

Innovative signal and power connection solutions for alternative powertrain concepts - Fröhlig, Simon; Piechulek, Niklas; Friedlein, Matthias; Süß-Wolf, Robert; Schmidt, Lorenz; Kuhn, Marlene; Wang, Li; Hefner, Florian; Heisler, Paul; Fröhlich, Jan; Meiners, Moritz; Franke, Jörg (2020 10th International Electric Drives Production Conference (EDPC), 2020)
Since the automotive wiring harness interconnects all electrical components in a vehicle, it also must adapt to all componential, mechanical, and electrical architecture changes. For this reason, almost all trends that affect the vehicle in general also affect the wiring system. This paper describes the current situation, analyses the most important trends in the automotive industry, and discusses their effects on the wiring system. In particular, the focus is on the current megatrend of electromobility and the associated electrification of the powertrain. In addition to the integration of autonomous driving functions and Car-To-X- Communication, the electrification adds new requirements and tasks for the wire harness. In this context, a holistic approach is taken to combine various fields of research such as automation solutions, computer-aided technologies, functional integration, as well as reliability models to offer a solution for the challenges caused by current automotive trends.<br
Keywords: electromobility; wiring harness; vehicle electrical system; signal and power connection; alternative powertrain

Investigating Laser Direct Structuring and Aerosol-Jet for Additively Manufactured Helix Antennas - Ankenbrand, Markus; Panusch, David; Piechulek, Niklas; Gold, Gerald; Helmreich, Klaus; Franke, Jörg (2024 International Conference on Electronics Packaging, ICEP 2024, 2024)
This paper investigates the manufacturing of helix antennas using additive technologies, highlighting the influences of substrate surface quality and manufacturing processes on antenna characteristics. The focus lies on Fused Filament Fabrication and Digital Light Synthesis for the substrate generation, and Aerosol-Jet and Laser Direct Structuring (LDS) for functional structuring. The tested materials are PEEK, epoxy and polycarbonate for the substrate and silver and copper for the traces. Challenges encountered during manufacturing include spreading of the ink in Aerosol-Jet printing, and short circuits caused by smoke residues in LDS. The radiation patterns of the additively manufactured antennas are compared with simulated responses and a subtractively manufactured reference, revealing a small but measurable impact of geometric deviations and surface roughness on performance.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Additive Manufacturing; Helix Antenna; Laser Direct Structuring; Printed Electronics

Machine Learning Based Quality Prediction for Solder Paste Dispensing in Electronics Production - Thielen, Nils; Pan, Wenzhe; Piechulek, Niklas; Voigt, Christian; Meier, Sven; Schmidt, Konstantin; Franke, Jörg (Proceedings of the 24th Electronics Packaging Technology Conference, EPTC 2022, 2022)
Transfer of solder paste for manufacturing of electronic assemblies is a crucial process step for final product quality. While the most common technologies are stencil- and screen-printing, dispensing of solder paste can be seen as an alternative, especially for three-dimensional circuit carriers and small-scale production. Nonetheless, dispensing lacks in process speed and suffers from anomalies in the process, such as insufficient solder paste transfer. In this paper, we investigated a data-driven approach to predict quality of these solder depots in terms of height, area and volume including both process data and previous dispensing quality itself. This work contains three steps. First, a suitable data set was generated by means of Design of Experiment and the dispensing steps based on it. The data was first statistically analyzed. For the model development primarily using automated machine learning (AutoML) is chosen as an approach, in order to reduce model development time and hyperparameter tuning. Furthermore, a deep neural network is trained as a comparison. The performance of the AutoML model ensemble outperforms both the neural network and the statistical benchmark for all quality parameters considered: height, area and volume of the deposited solder paste. The best models offer an R2 score of 0.71 for height, 0.89 for area and 0.81 for solder paste volume, on a separated test dataset. Thus, indicating strong correlation.
CRIS-Team Scopus Importer:2023-03-07

Miniaturization Potential of Additive-Manufactured 3D Mechatronic Integrated Device Components Produced by Stereolithography - Piechulek, Niklas; Xu, Lei; Fröhlich, Jan; Bründl, Patrick; Franke, Jörg (Micromachines, 2025)
Three-dimensional Mechatronic Integrated Devices (3D-MIDs) combine mechanical and electrical functions, enabling significant component miniaturization and enhanced functionality. However, their application in high-temperature environments remains limited due to material challenges. Existing research highlights the thermal stability of ceramic substrates; yet, their reliability under high-stress and complex mechanical loading conditions remains a challenge. In this study, 3D-MID components were fabricated using stereolithography (SLA) 3D-printing technology, and the feasibility of circuit miniaturization on high-temperature-resistant resin substrates was explored. Additionally, the influence of laser parameters on resistance values was analyzed using the Response Surface Methodology (RSM). The results demonstrate that SLA 3D-printing achieves substrates with low surface roughness, enabling the precise formation of fine features. Electric circuits are successfully formed on substrates printed with resin mixed with Laser Direct Structuring (LDS) additives, following laser structuring and metallization processes, with a minimum conductor spacing of 150 µm. Furthermore, through the integration of through-holes (vias) and the use of smaller package chips, such as Ball Grid Array (BGA) and Quad Flat No-lead (QFN), the circuits achieve further miniaturization and establish reliable electrical connections via soldering. Taken together, our results demonstrate that thermoset plastics serve as substrates for 3D-MID components, broadening the application scope of 3D-MID technology and providing a framework for circuit miniaturization on SLA-printed substrates.
CRIS-Team Scopus Importer:2025-02-07
Keywords: laser direct structuring; mechatronic integrated devices; MID; miniaturization; SLA

Reliable and Automated Connection of Printed Electronics to the Aviation Electrical System - Fröhlich, Jan; Piechulek, Niklas; Nguyen, Huong Giang; Franke, Jörg; Jurgenhake, Christoph (2024 Pan Pacific Strategic Electronics Symposium, Pan Pacific 2024, 2024)
In recent years, numerous applications for printed electronics have been successfully implemented. Heating elements, sophisticated circuits, sensors, and antennas can be printed on a broad bandwidth of materials and three-dimensional surfaces. Several projects investigated the use of printed electronics in the aviation industry and demonstrated the applicability of printed structures on aerospace substrates. Printed systems were implemented to improve maintenance and passenger comfort and the automated repair of printed structures was proven. However, the reliability and contacting of the printed structures still is a major challenge. Especially for the use of printed electronics in the aviation industry, this research gap needs to be addressed. Therefore, a new research project investigates the reliable connection of printed electronics to the aviation electrical system. This research aims to find a solution that offers good electrical characteristics, is reliable, and can be manufactured in an automated way. To meet the requirements of the aviation industry, experts are consulted and a detailed catalog of requirements is drawn up. Preliminary tests were carried out in which connector elements were glued to the cabin linings and inserted into the substrate. The findings show that only concepts in which the connector is inserted into the substrate and glued, riveted, or screwed offer the necessary mechanical stability. Based on the experience from the preliminary tests and the catalog of requirements, a concept is developed that provides for the integration of a market-Available and aviation-Approved connector into the substrate of the cabin lining. To test the concept, a circuit is developed and implemented as a prototype. The most important electrical characteristic is the contact resistance of the connection. The goal is to produce a contact point with less than 1.0 Ω contact resistance. The measurement is conducted using the four-point method. The mechanical characterization of the prototypes is carried out using tensile tests and shear tests. The requirements for assessing the reliability are derived from the aviation requirements for mechatronic components. To meet the requirements, the demonstrator must withstand a temperature change from +80 °C to-40 °C in 10 cycles of 10 hours each and a load of 1000 mating cycles, with a change in contact resistance of a maximum of 5%. While the prototype is being characterized electrically and mechanically and its reliability is being tested, a concept for the automated integration of the connector into the aviation substrates must be developed. The printed circuit is produced in a five-Axis CNC machine in which three-dimensional workpieces can be processed from almost all sides. The machine can also be flexibly equipped with numerous tools. In addition to systems for producing printed circuits such as piezo jet, aerosol jet, pick and place, and sintering systems, a milling machine can also be integrated. Therefore, the goal is to produce the printed circuit including the connection fully automatically in the five-Axis CNC machine.
CRIS-Team Scopus Importer:2024-03-15
Keywords: automation; aviation; connection; contacting; manufacturing process; printed electronics; reliability